2013
DOI: 10.1073/pnas.1310655110
|View full text |Cite
|
Sign up to set email alerts
|

Social stress up-regulates inflammatory gene expression in the leukocyte transcriptome via β-adrenergic induction of myelopoiesis

Abstract: Significance Chronic exposure to adverse social environments is associated with increased risk of disease, and stress-related increases in the expression of proinflammatory genes appear to contribute to these effects. The present study identifies a biological mechanism of such effects in the ability of the sympathetic nervous system to up-regulate bone marrow production of immature, proinflammatory monocytes. These effects are mediated by β-adrenergic receptors and the myelopoietic growth factor GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
510
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 510 publications
(564 citation statements)
references
References 63 publications
48
510
5
1
Order By: Relevance
“…It also remains to be determined which neurobiological pathways mediate the effects of prosocial behavior. This is a particularly intriguing question in light of previous data showing that CTRA expression is biologically mediated in large part by threat-related systems (i.e., sympathetic nervous system/β-adrenergic signaling; Cole, 2014;Cole et al, 2015a;Powell et al, 2013). Defining the upstream neurobiological mediators in the CNS substrates of prosocial experience also remains an important topic for future research (Eisenberger and Cole, 2012).…”
Section: Psychobiological Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…It also remains to be determined which neurobiological pathways mediate the effects of prosocial behavior. This is a particularly intriguing question in light of previous data showing that CTRA expression is biologically mediated in large part by threat-related systems (i.e., sympathetic nervous system/β-adrenergic signaling; Cole, 2014;Cole et al, 2015a;Powell et al, 2013). Defining the upstream neurobiological mediators in the CNS substrates of prosocial experience also remains an important topic for future research (Eisenberger and Cole, 2012).…”
Section: Psychobiological Mechanismsmentioning
confidence: 98%
“…This research has identified a conserved transcriptional response to adversity (CTRA) in circulating leukocytes that is characterized by up-regulation of pro-inflammatory genes and down-regulation of genes involved in innate antiviral responses and antibody production (Cole, 2014;Slavich and Cole, 2013). The CTRA gene expression profile is mediated by both per-cell alterations in gene transcription and increased production of specific subtypes of leukocytes (particularly myeloid lineage monocytes and dendritic cells; Cole et al, 2011;Cole, 2014;Powell et al, 2013;Slavich and Cole, 2013). These dynamics are mediated by activation of β-adrenergic signaling pathways in response to sympathetic nervous system activity and take place over the course of several hours to a few days (Cole, 2010(Cole, , 2014Cole et al, 2015a;Powell et al, 2013;Slavich and Cole, 2013).…”
Section: Human Social Genomicsmentioning
confidence: 99%
“…76 In addition, animal research in mice has identified upregulation of inflammatory gene expression in the presence of social stress. 77 …”
Section: The Pathophysiology Of Poverty Toxic Stressmentioning
confidence: 99%
“…Epigenetic or other alterations in response to stress during "critical periods" of growth and development may modify brain function, and thus sensitize neural responsiveness to traumatic situations later in life. For instance, under stressful conditions, the persistently sensitized brain may elicit a heightened sympathetic nervous system response-the response associated with fight-or-flight-which has been shown to up-regulate sub-populations of immature monocytes, prompting increased leukocyte expression of proinflammatory genes (Powell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%